World Small Animal Veterinary Association Renal Pathology Initiative: Classification of Glomerular Diseases in Dogs. (January 2016) - Cianciolo, R. E.; Mohr, F. C.; Aresu, L.; Brown, C. A.; James, C.; Jansen, J. H.; Spangler, W. L.; van der Lugt, J. J.; Kass, P. H.; Brovida, C.; Cowgill, L. D.; Heiene, R.; et al.
Evaluation of canine renal biopsy tissue has generally relied on light microscopic (LM) evaluation of hematoxylin and eosin–stained sections ranging in thickness from 3 to 5 µm. Advanced modalities, such as transmission electron microscopy (TEM) and immunofluorescence (IF), have been used sporadically or retrospectively. Diagnostic algorithms of glomerular diseases have been extrapolated from the World Health Organization classification scheme for human glomerular disease. With the recent establishment of 2 veterinary nephropathology services that evaluate 3-µm sections with a panel of histochemical stains and routinely perform TEM and IF, a standardized objective species-specific approach for the diagnosis of canine glomerular disease was needed. Eight veterinary pathologists evaluated 114 parameters (lesions) in renal biopsy specimens from 89 dogs. Hierarchical cluster analysis of the data revealed 2 large categories of glomerular disease based on the presence or absence of immune complex deposition: The immune complex–mediated glomerulonephritis (ICGN) category included cases with histologic lesions of membranoproliferative or membranous patterns. The second category included control dogs and dogs with non-ICGN (glomerular amyloidosis or focal segmental glomerulosclerosis). Cluster analysis performed on only the LM parameters led to misdiagnosis of 22 of the 89 cases—that is, ICGN cases moved to the non-ICGN branch of the dendrogram or vice versa, thereby emphasizing the importance of advanced diagnostic modalities in the evaluation of canine glomerular disease. Salient LM, TEM, and IF features for each pattern of disease were identified, and a preliminary investigation of related clinicopathologic data was performed.